Integration of SCOR Model and AHP to Measure the Shipyard Supply Chain Performance: A Case Study - Tutuhatunewa, Alfredo; Maitimu, Nil Edwin; Hukunala, Lely Marlen (Institute of Research and Community Outreach - Petra Christian University, 2023)
A shipyard is an industry engaged in the construction or repair of ships. A shipyard's ability to complete its production depends on the supply chain. Its suppliers supply all the equipment and materials needed for shipbuilding and maintenance. The shipbuilding sector's supply chain's performance level must be measured to determine how well the existing process flow works. The research was conducted at the PT Dock and a shipyard company in Maluku, Indonesia. The measurement integrates the SCOR and AHP models to determine the existing supply chain performance. The data are collected through questionnaires and from the company archives. The study's findings demonstrate how simple it is to integrate the SCOR model with AHP to assess the shipbuilding sector's supply chain performance. The research proposes 21 KPIs. Those KPIs are constructed from literature studies and interviews with shipyard management. One of the AHP findings in this study states that the most important phase in the shipbuilding industry's supply chain is planning.